PENERAPAN METODE FORECASTING DALAM PERENCANAAN PRODUKSI BAKPIA DENGAN MENGGUNAKAN SOFTWARE POM GUNA MEMENUHI PERMINTAAN KONSUMEN - Junaedi, Didik; Mas'ud, M. Imron (Journal Knowledge Industrial Engineering (JKIE), 2018)
Home Industry has limited resources and a variety of suggestions (Multi Objective) to be obtained. The goal to be achieved is to maximize the amount of production, maximize profits, drink working hours and minimize the use of hours and minimize the use of raw materials. Forecasting (forecasting) is an attempt to estimate what happens in the future based on previous data or past data, which is based on scientific and qualitative methods carried out systematically, this study aims to find the exact value of the method predicted by looking at MAPE, MAD, MSE values ​​who want to achieve UKM Siti Khotijah.